Anti-solvent-resistant trans-perovskite solar cell and preparation method thereof

By replacing traditional toxic anti-solvents with green anti-solvent dimethyl carbonate, environmental and health problems in the preparation of perovskite solar cells are solved, and the preparation of high-quality perovskite films and significant improvements in the performance of perovskite solar cells are achieved.

CN119630253AInactive Publication Date: 2025-03-14JILIN UNIVERSITY
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202510158889.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The toxic anti-solvent used by traditional perovskite solar cells during preparation causes environmental and health problems, and perovskite solar cells using green anti-solvents are lower than traditional methods in terms of performance.

Method used

Green anti-solvent dimethyl carbonate is used to replace traditional highly toxic chlorobenzene anti-solvents, and high-quality perovskite films are prepared by adjusting the morphology, controlling the thickness and optimizing the grain boundaries.

Benefits of technology

The crystal quality, flatness and density of perovskite films are improved, and the energy loss caused by leakage current loss and non-radiative recombination are reduced, which significantly improves the current density, open circuit voltage, fill factor, power conversion efficiency and stability of perovskite solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119630253A_ABST
    Figure CN119630253A_ABST
Patent Text Reader

Abstract

The invention is suitable for the technical field of perovskite solar cells, and provides an anti-solvent-resistant trans-perovskite solar cell and a preparation method thereof. The green anti-solvent dimethyl carbonate is used for replacing the traditional high-toxicity chlorobenzene anti-solvent, so that the problem of environmental pollution in the preparation process of the perovskite solar cell is solved. The prepared perovskite thin film is larger in grain size, higher in crystallization quality, fewer in defect and higher in flatness and density, most leakage current loss is reduced, energy loss caused by non-radiative recombination is restrained, and the current density of the perovskite solar cell is greatly improved. According to the perovskite solar cell, the carrier transmission problem is improved, carrier recombination between perovskite and the electron transmission layer is inhibited, and therefore the open-circuit voltage, the filling factor, the power conversion efficiency, the stability and the like of the perovskite solar cell are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of perovskite solar cells, and in particular relates to an anti-solvent-based inverse perovskite solar cell and a preparation method thereof. Background Art

[0002] Perovskite solar cells have attracted extensive attention due to their high absorption coefficient, long carrier diffusion length, adjustable bandgap, low temperature and non-vacuum preparation processes. In the past 15 years, the power conversion efficiency (PCE) of single-junction perovskite solar cells has increased from 3.8% to 26.09%, showing good commercial prospects. It is well known that high-quality perovskite films are the key to high-performance perovskite solar cells. However, defects in perovskites in the body and at grain boundaries are extremely unfavorable to perovskite solar cells because they can induce very serious non-radiative recombination.

[0003] The antisolvent-assisted crystallization method is an effective technique to improve the quality of perovskite films, including adjusting morphology, controlling thickness, and optimizing grain boundaries. Different antisolvents may lead to different initial nucleation and subsequent growth and crystallization due to their different physical (including boiling point, dipole moment, viscosity, surface tension, density, etc.) and chemical properties (solubility, miscibility, and polarity). Selecting an antisolvent with suitable physical and chemical properties can regulate nucleation and crystallization, resulting in compact, smooth, and high-quality perovskite films.

[0004] Antisolvents such as toluene, chlorobenzene and chloroform are widely used in the preparation of traditional perovskite solar cells. Due to their non-negligible toxicity, they cause environmental and health problems, which seriously affect the sustainable development of perovskite solar cells. At present, the average and optimal device performance of perovskite solar cells prepared using pure green antisolvents or mixed green antisolvents is still lower than that of perovskite solar cells using traditional toxic antisolvents, such as the most commonly used chlorobenzene antisolvent. Therefore, there is an urgent need to explore more green and efficient antisolvents to replace toxic antisolvents in order to achieve the goal of sustainable development. To this end, the present invention proposes an antisolvent-based trans-perovskite solar cell and a preparation method thereof. The present invention uses the green antisolvent dimethyl carbonate to replace the traditional highly toxic chlorobenzene antisolvent.

[0005] The Chinese invention patent with publication number CN116367559A discloses a method for preparing a tin-based perovskite solar cell. Although the claims disclose that the anti-solvent can be selected from dimethyl carbonate, chlorobenzene is used as the anti-solvent in the embodiments of the specification. The claims are not based on the specification, and there is no detailed description of how to use the anti-solvent, nor is there any study on the effect of the anti-solvent on the preparation of perovskite film or perovskite solar cell devices. The Chinese invention patent with publication number CN108389969A discloses a green solvent system and mixed solution for preparing a perovskite layer of a perovskite solar cell. It uses dimethyl carbonate and N-methylpyrrolidone as solvents for dissolving perovskite powder, replacing solvents such as DMF and DMSO. The present invention uses dimethyl carbonate as an anti-solvent to promote perovskite crystallization when spin-coating perovskite, and the two have completely different effects. Summary of the invention

[0006] The object of the present invention is to provide an anti-solvent based inverse perovskite solar cell and a preparation method thereof, aiming to solve the problems raised in the above background technology.

[0007] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a solvent-resistant inverse perovskite solar cell comprises the following steps: A transparent substrate is provided; a transparent conductive anode is formed on the transparent substrate; a hole transport layer is formed on the transparent conductive anode; a self-assembled monolayer is formed on the hole transport layer; a perovskite light absorption layer is formed on the self-assembled monolayer; a two-dimensional passivation layer is formed on the perovskite light absorption layer; an electron transport layer is formed on the two-dimensional passivation layer; a hole blocking layer is formed on the electron transport layer; and a metal cathode is formed on the hole blocking layer; The preparation process of the perovskite light-absorbing layer is as follows: N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) are mixed at a volume ratio of 780-820:180-220 to obtain a mixed solvent; then lead iodide (PbI2), cesium iodide (CsI), formamidine iodide (FAI), methylamine iodide (MAI), and methylamine chloride (MACl) are added to the mixed solvent at molar ratios of 1.48-1.52, 0.07-0.08, 1.27-1.28, 0.14-0.16, and 0.12-0.18, respectively. After stirring for 1.5-2h, a perovskite precursor was obtained. The perovskite precursor was first rotated at 1000rpm for 5s and then at 5000rpm for 35s before being coated on the self-assembled monolayer. Ten seconds before the end of the spin coating, in order to compare the effects of different antisolvents, traditional highly toxic antisolvent chlorobenzene (CB), green antisolvent ethyl acetate (EA), dimethyl carbonate (DMC), diethyl carbonate (DEC) or dipropyl carbonate (DPC) were dropped into the center of the film, and annealed at 100°C for 30min to form a perovskite light-absorbing layer.

[0008] The molecular structure of the traditional highly toxic anti-solvent chlorobenzene is as follows: ; The molecular structure of the green antisolvent ethyl acetate is as follows: ; The molecular structure of green antisolvent dimethyl carbonate is as follows: ; The molecular structure of green antisolvent diethyl carbonate is as follows: ; The molecular structure of green antisolvent dipropyl carbonate is as follows: .

[0009] Furthermore, the chemical formula of ethyl acetate is C4H8O2; the chemical formula of dimethyl carbonate is C3H6O3; the chemical formula of diethyl carbonate is C5H 10 O3; dipropyl carbonate, chemical formula is C7H 14 O3. They are low-toxic, environmentally friendly and widely used chemical raw materials, and are important organic synthesis intermediates. Their molecular structures contain carbonyl, methyl, ethyl, propyl, methoxy, ethoxy and propoxy functional groups, and they have a variety of reaction properties. They are safe, convenient, less polluting and easy to transport in production.

[0010] Furthermore, the transparent substrate is a transparent glass substrate, and the transparent glass substrate is a quartz glass, silicate glass or soda-lime glass substrate.

[0011] Furthermore, the preparation process of the transparent conductive anode is: depositing a layer of indium-doped tin oxide (ITO) as the transparent conductive anode on a transparent substrate by magnetron sputtering technology.

[0012] Furthermore, the hole transport layer is prepared by spin coating nickel oxide (NiO X , concentration is 10 mg / mL, solvent is deionized water) at 2000 rpm for 30 s and annealed at 150 °C for 30 min to form a hole transport layer.

[0013] Furthermore, the preparation process of the self-assembled monolayer is as follows: on the hole transport layer, [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz, concentration is 0.5 mg / mL, solvent is anhydrous ethanol) is rotated at 5000 rpm for 30 seconds by spin coating, and annealed at 100°C for 10 minutes to form a self-assembled monolayer.

[0014] Furthermore, the preparation process of the two-dimensional passivation layer is as follows: on the perovskite light-absorbing layer, phenylethylamine iodide (PEAI, concentration is 2 mg / mL, solvent is isopropanol) is spin-coated at 5000 rpm for 35 seconds, and annealed at 100°C for 5 minutes to form a two-dimensional passivation layer.

[0015] Furthermore, the preparation process of the electron transport layer is as follows: on the two-dimensional passivation layer, [6,6]-phenyl-C61-butyric acid methyl ester (PC 61 BM, concentration of 20 mg / mL, solvent: chlorobenzene) was spun at 2000 rpm for 40 s and annealed at 70 °C for 5 min to form an electron transport layer.

[0016] Furthermore, the preparation process of the hole blocking layer is as follows: on the electron transport layer, 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP, concentration is 0.5 mg / mL, solvent is isopropanol) is rotated at 5000 rpm for 30 seconds by spin coating, and annealed at 70°C for 5 minutes to form a hole blocking layer.

[0017] Furthermore, the preparation process of the metal cathode is as follows: on the hole blocking layer, a layer of silver (Ag) with a thickness of 80-100 nm is deposited by vacuum evaporation technology as the metal cathode.

[0018] A solvent-resistant inverse perovskite solar cell prepared according to the preparation method described above.

[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses the green antisolvent dimethyl carbonate instead of the traditional highly toxic chlorobenzene antisolvent to solve the environmental pollution problem in the process of preparing perovskite solar cells.

[0020] 2. The perovskite film prepared by the present invention has a larger grain size, higher crystal quality, fewer defects, higher flatness and density, reduces most of the leakage current loss, inhibits the energy loss caused by non-radiative recombination, and greatly improves the current density of perovskite solar cells.

[0021] 3. The present invention improves the carrier transport problem and inhibits the carrier recombination between the perovskite and the electron transport layer, thereby greatly improving the open circuit voltage, fill factor, power conversion efficiency and stability of the perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a schematic diagram of the structure of an inverted perovskite solar cell prepared by the present invention.

[0023] Figure 2 Surface scanning electron microscopic images of the perovskite films prepared in Example 1 and Comparative Example 1 of the present invention; wherein (a) is the perovskite film prepared in Comparative Example 1, and (b) is the perovskite film prepared in Example 1.

[0024] Figure 3 The cross-sectional scanning electron micrographs of the perovskite films prepared in Example 1 and Comparative Example 1 of the present invention; (a) is the perovskite film prepared in Comparative Example 1, and (b) is the perovskite film prepared in Example 1.

[0025] Figure 4 XRD diagrams of the perovskite films prepared in Example 1 and Comparative Example 1 of the present invention.

[0026] Figure 5 The UV-visible absorption spectra of the perovskite films prepared in Example 1 and Comparative Example 1 of the present invention.

[0027] Figure 6 The current-voltage curves of the pure electron device and the pure hole device prepared in Example 1 and Comparative Example 1 of the present invention measured in the dark state; (a) is a pure electron device, and (b) is a pure hole device.

[0028] Figure 7 1 is the current density-voltage curve of the perovskite solar cell prepared in Examples 1 to 6 of the present invention and Comparative Example 1.

[0029] Figure 8 The long-term stability of the perovskite solar cells prepared in Example 1 and Comparative Example 1 of the present invention in air. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0031] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0032] Example 1: The preparation method of a trans-perovskite solar cell using 200 μL dimethyl carbonate antisolvent is as follows: 1) The transparent substrate (ITO) with a transparent conductive anode is ultrasonically cleaned, dried and plasma treated; 2) NiO X The nanoparticles were dispersed in deionized water at a concentration of 10 mg / mL to form NiO X Ink. The prepared NiO X The ink was spin-coated on a transparent conductive anode at 2000 rpm for 30 s and then annealed in air at 150 °C for 30 min to obtain a hole transport layer.

[0033] 3) MeO-2PACz was dissolved in anhydrous ethanol at a concentration of 0.5 mg / mL, spin-coated on the hole transport layer at 5000 rpm for 30 s, and annealed at 100°C for 10 min to obtain a self-assembled monolayer.

[0034] 4) DMF and DMSO were mixed in a volume ratio of 800:200 to obtain a mixed solvent; PbI2, CsI, FAI, MAI, and MACl were then added to the mixed solvent in molar ratios of 1.5, 0.075, 1.275, 0.15, and 0.15, respectively, and stirred for 2 hours to obtain a perovskite precursor; the perovskite precursor was first rotated at 1000 rpm for 5 seconds and then at 5000 rpm for 35 seconds to coat the self-assembled monolayer. 10 seconds before the end of the spin coating, 200 µL of dimethyl carbonate was dropped into the center of the film, and annealed at 100 ° C for 30 minutes to obtain a perovskite light-absorbing layer.

[0035] 5) PEAI was dissolved in isopropanol at a concentration of 2 mg / mL, spin-coated on the perovskite light-absorbing layer at 5000 rpm for 35 s, and annealed at 100 °C for 5 min to obtain a two-dimensional passivation layer.

[0036] 6) Connect the PC 61 BM was dissolved in chlorobenzene at a concentration of 20 mg / mL, spin-coated on the two-dimensional passivation layer at 2000 rpm for 40 s, and annealed at 70 °C for 5 min to obtain the electron transport layer.

[0037] 7) BCP was dissolved in isopropanol at a concentration of 0.5 mg / mL, spin-coated on the electron transport layer at 5000 rpm for 30 s, and annealed at 70 °C for 5 min to obtain a hole blocking layer.

[0038] 8) In a vacuum evaporator, evaporate the metal cathode Ag on the hole blocking layer with a thickness of 80~100nm. This completes the entire preparation process of the green anti-solvent-based inverse perovskite solar cell, and the effective area of ​​the cell is 0.05cm 2 .

[0039] Comparative Example 1: The preparation method of a trans-perovskite solar cell using 200 µL of chlorobenzene antisolvent is as follows: Except for the difference in the preparation method of step 4) the perovskite light absorption layer, the other preparation processes are the same as those in Example 1.

[0040] The antisolvent used in step 4) of this control example is 200 μL of chlorobenzene. The other operations are the same as those in Example 1.

[0041] Example 2: The method for preparing a trans-perovskite solar cell using 150 μL of green antisolvent dimethyl carbonate is as follows: Except for the difference in the preparation method of step 4) the perovskite light absorption layer, the other preparation processes are the same as those in Example 1.

[0042] The antisolvent used in step 4) of this embodiment is 150 μL dimethyl carbonate. Other operations are the same as those in Example 1.

[0043] Example 3: The preparation method of a trans-perovskite solar cell using 250 μL dimethyl carbonate antisolvent is as follows: Except for the difference in the preparation method of step 4) the perovskite light absorption layer, the other preparation processes are the same as those in Example 1.

[0044] The antisolvent used in step 4) of this embodiment is 250 μL dimethyl carbonate. Other operations are the same as those in Example 1.

[0045] Example 4: The method for preparing a trans-perovskite solar cell using 200 μL of ethyl acetate antisolvent is as follows: Except for the difference in the preparation method of step 4) the perovskite light absorption layer, the other preparation processes are the same as those in Example 1.

[0046] The antisolvent used in step 4) of this embodiment is 200 μL of ethyl acetate. Other operations are the same as those in Example 1.

[0047] Example 5: The preparation method of a trans-perovskite solar cell using 200 μL diethyl carbonate antisolvent is as follows: Except for the difference in the preparation method of step 4) the perovskite light absorption layer, the other preparation processes are the same as those in Example 1.

[0048] The antisolvent used in step 4) of this embodiment is 200 μL diethyl carbonate. Other operations are the same as those in Example 1.

[0049] Example 6: The preparation method of a trans-perovskite solar cell using 200 μL dipropyl carbonate antisolvent is as follows: Except for the difference in the preparation method of step 4) the perovskite light absorption layer, the other preparation processes are the same as those in Example 1.

[0050] The antisolvent used in step 4) of this embodiment is 200 μL of dipropyl carbonate. Other operations are the same as those in Example 1.

[0051] The following performance tests were performed: Perovskite film surface morphology and cross-sectional morphology testing; Figure 2 The surface scanning electron micrographs of the perovskite film prepared using chlorobenzene antisolvent (a) in Control Example 1 and dimethyl carbonate antisolvent (b) in Example 1 are shown. As can be seen from the figure, the perovskite film prepared using dimethyl carbonate antisolvent has a larger grain size, a smoother surface, and fewer defect holes.

[0052] Figure 3 The cross-sectional scanning electron micrographs of the perovskite film prepared using chlorobenzene antisolvent (a) in Control Example 1 and dimethyl carbonate antisolvent (b) in Example 1 are shown. As can be seen from the figure, the perovskite layer prepared using dimethyl carbonate antisolvent is more dense.

[0053] X-ray diffraction (XRD) test and UV-visible absorption test of the crystal quality of perovskite films; Figure 4 The XRD patterns of the perovskite film prepared using chlorobenzene antisolvent in Control Example 1 and dimethyl carbonate antisolvent in Example 1 are shown in Figure 1. It can be seen from the figure that the perovskite grains mainly grow along the (110) direction, and the increase in the (110) peak diffraction intensity indicates that the perovskite film prepared using dimethyl carbonate antisolvent has higher crystalline quality.

[0054] Figure 5 The UV-visible absorption spectra of the perovskite film prepared using chlorobenzene antisolvent in Control Example 1 and dimethyl carbonate antisolvent in Example 1. As can be seen from the figure, the perovskite film prepared using dimethyl carbonate antisolvent has stronger visible light absorption.

[0055] Defect state testing of perovskite films; Figure 6The current-voltage curves of the pure electronic device (a) and the pure hole device (b) prepared in the dark state using chlorobenzene antisolvent in Control Example 1 and dimethyl carbonate antisolvent in Example 1 are shown in Figure 1. The structure of the pure electronic device is: ITO / tin oxide (SnO2) / perovskite (Perovskite) / PCBM / Ag; the structure of the pure hole device is: ITO / NiO X / MeO-2PACz / Perovskite / 2,2',7,7'-Tetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) / Ag. As can be seen from the figure, the perovskite prepared using dimethyl carbonate antisolvent has a lower defect density, thereby effectively suppressing the energy loss caused by non-radiative recombination.

[0056] Efficiency testing of perovskite solar cells; Figure 7 The perovskite solar cells prepared by using chlorobenzene antisolvent in control example 1, dimethyl carbonate antisolvent in examples 1 to 3, ethyl acetate antisolvent in example 4, diethyl carbonate antisolvent in example 5 and dipropyl carbonate antisolvent in example 6 were placed at 100 mW / cm 2 The solar cell efficiency test was carried out under a solar simulator with a light intensity of AM1.5G. The photovoltaic parameters of each sample are shown in Table 1: Table 1 Implementation No. Solvent resistance oc (V) <![CDATA[ J sc (mA / cm 2 )]]> FF (%) PCE (%) Comparative Example 1 200µL Chlorobenzene 1.151 24.74 81.72 23.26 Example 1 200µL dimethyl carbonate 1.180 25.28 84.42 25.18 Example 2 150µL dimethyl carbonate 1.183 24.94 83.34 24.58 Example 3 250µL dimethyl carbonate 1.175 25.04 83.23 24.50 Example 4 200 µL ethyl acetate 1.167 24.91 83.30 24.22 Example 5 200µL diethyl carbonate 1.176 24.98 82.74 24.32 Example 6 200µL dipropyl carbonate 1.172 24.87 81.11 23.64 As shown in Table 1, the perovskite solar cell prepared using 200µL dimethyl carbonate antisolvent achieved a high efficiency of 25.18%. The main improvement of the cell comes from the open circuit voltage ( V oc) increased from 1.151V to 1.180V and the fill factor (FF) increased from 81.72% to 84.42%, indicating that the defect density in the battery is reduced, reducing the open circuit voltage loss caused by non-radiative recombination and promoting the transport and extraction of carriers. The short-circuit current ( J sc) from 24.74 mA / cm 2 Increased to 25.28mA / cm 2 , which is due to the higher crystal quality and larger grain size of perovskite.

[0057] Stability testing of perovskite solar cells; Figure 8The long-term stability of the perovskite solar cell prepared in the air by using chlorobenzene antisolvent in Control Example 1 and dimethyl carbonate antisolvent in Example 1. As can be seen from the figure, the stability of the perovskite solar cell prepared in Control Example 1 after aging in the air for about 400 hours, and the stability of the perovskite solar cell prepared in Example 1 after aging in the air for about 1000 hours. It shows that the long-term stability of the perovskite solar cell prepared by using dimethyl carbonate antisolvent in the air is significantly improved.

[0058] In summary, the present invention compares the effects of using traditional highly toxic anti-solvent chlorobenzene, green anti-solvent ethyl acetate, dimethyl carbonate, diethyl carbonate and dipropyl carbonate to prepare perovskite cells. Finally, the inverse perovskite solar cell prepared using the green anti-solvent dimethyl carbonate can show excellent photoelectric performance, with a power conversion efficiency (PCE) of 25.18%, and 91% of the initial efficiency after aging in air for about 1000 hours.

[0059] The above are only preferred embodiments of the present invention. It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention. These should also be regarded as the protection scope of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.

Claims

1. A method for preparing a solvent-resistant inverse perovskite solar cell, characterized in that: The following steps are involved: Providing a transparent substrate; forming a transparent conductive anode on the transparent substrate; forming a hole transport layer on the transparent conductive anode; forming a self-assembled monolayer on the hole transport layer; forming a perovskite light-absorbing layer on the self-assembled monolayer; forming a two-dimensional passivation layer on the perovskite light-absorbing layer; forming an electron transport layer on the two-dimensional passivation layer; forming a hole blocking layer on the electron transport layer; and forming a metal cathode on the hole blocking layer; The preparation process of the perovskite light-absorbing layer is as follows: DMF and DMSO are mixed in a volume ratio of 780~820:180~220 to obtain a mixed solvent; then PbI2, CsI, FAI, MAI, and MACl are added to the mixed solvent in molar ratios of 1.48~1.52, 0.07~0.08, 1.27~1.28, 0.14~0.16, and 0.12~0.18, respectively, and stirred for 1.5~2h to obtain a perovskite precursor; the perovskite precursor is first rotated at 1000rpm for 5s, and then rotated at 5000rpm for 35s to coat the self-assembled monolayer, and 10s before the end of the spin coating, 200µL of dimethyl carbonate is dropped into the center of the film, and annealed at 100°C for 30min to form a perovskite light-absorbing layer.

2. The preparation method according to claim 1, characterized in that: The preparation process of the transparent conductive anode is as follows: a layer of indium-doped tin oxide is deposited on a transparent substrate by magnetron sputtering technology as the transparent conductive anode.

3. The preparation method according to claim 1, characterized in that: The preparation process of the hole transport layer is as follows: NiO is spin-coated on a transparent conductive anode. X The solution was rotated at 2000 rpm for 30 s and annealed at 150 °C for 30 min to form a hole transport layer; NiO X The concentration of the solution was 10 mg / mL, and the solvent was deionized water.

4. The preparation method according to claim 1, characterized in that: The preparation process of the self-assembled monolayer is as follows: on the hole transport layer, a MeO-2PACz solution is rotated at 5000 rpm for 30 seconds by spin coating, and annealed at 100° C. for 10 minutes to form a self-assembled monolayer; the concentration of the MeO-2PACz solution is 0.5 mg / mL, and the solvent is anhydrous ethanol.

5. The preparation method according to claim 1, characterized in that: The preparation process of the two-dimensional passivation layer is as follows: on the perovskite light-absorbing layer, the PEAI solution is rotated at 5000 rpm for 35 seconds by spin coating, and annealed at 100° C. for 5 minutes to form a two-dimensional passivation layer; the concentration of the PEAI solution is 2 mg / mL, and the solvent is isopropanol.

6. The preparation method according to claim 1, characterized in that: The preparation process of the electron transport layer is as follows: PC is coated on the two-dimensional passivation layer by spin coating. 61 The BM solution was rotated at 2000 rpm for 40 s and annealed at 70 °C for 5 min to form an electron transport layer; PC 61 The concentration of BM solution was 20 mg / mL, and the solvent was chlorobenzene.

7. The preparation method according to claim 1, characterized in that: The preparation process of the hole blocking layer is as follows: on the electron transport layer, the BCP solution is rotated at 5000 rpm for 30 seconds by spin coating, and annealed at 70° C. for 5 minutes to form a hole blocking layer; the concentration of the BCP solution is 0.5 mg / mL, and the solvent is isopropanol.

8. The preparation method according to claim 1, characterized in that: The preparation process of the metal cathode is as follows: on the hole blocking layer, a layer of Ag with a thickness of 80-100 nm is deposited by vacuum evaporation technology as the metal cathode.

9. An anti-solvent based inverse perovskite solar cell prepared according to the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Green solvent system for preparing perovskite layer of perovskite solar cell and mixed solution

    CN108389969A

  • Preparation method of tin-based perovskite solar cell

    CN116367559A

  • Method for widening processing window of a perovskite light absorption layer and planar perovskite solar cell

    CN112909183A

  • Tin-lead mixed perovskite solar cell

    CN113725363A

  • Preparation method of tin-based perovskite solar cell

    CN116322082A